Direct synthesis of sulfide capped CdS and CdS/ZnS colloidal nanocrystals for efficient hydrogen evolution under visible light irradiation. Issue 34 (15th August 2018) - Fan, Xiang-Bing; Yu, Shan; Wu, Hao-Lin; Li, Zhi-Jun; Gao, Yu-Ji; Li, Xu-Bing; Zhang, Li-Ping; Tung, Chen-Ho; Wu, Li-Zhu
Abstract : CdS and CdS/ZnS colloidal nanocrystals (NCs) capped with inorganic sulfide (S 2− ) ligands were directly synthesized with no aid of organic ligands in water. Abstract : CdS and CdS/ZnS colloidal nanocrystals (NCs) capped with inorganic sulfide (S 2− ) ligands were directly synthesized with no aid of organic ligands in water. The obtained CdS/ZnS-S 2− NCs show a surprising activity for hydrogen evolution with a rate of 1.61 mmol mg −1 h −1 and an internal quantum yield of 54% under 465 nm light irradiation.